Study on River System Flood Forecasting Scheme for Longtan Hydropower Station Interval in Hongshui River - DU Yong; FU Yupeng; WEI Yongjiang; LI Zongtai (Renmin Zhujiang)
Longtan Hydropower Station is a flood control project in the Pearl River Basin,but there is currently a lack of a comprehensive river system flood forecasting scheme.In order to give full play to the flood control and storage function of Longtan Hydropower Station,tributary control stations such as Leigongtan,Moyang,Pinglihe,Pinghu,and Xianrenqiao are selected,and the key areas of concern are determined through the analysis of important sub-intervals.The river system flood forecasting scheme for the Longtan Hydropower Station interval is constructed by using the Xin'an River three-source runoff generation model,three-source lag routing convergence model,and Maskingen convergence algorithm.The research results show that the proportion of the maximum inflow flood volume of Longtan Hydropower Station is usually in uncontrolled intervals,followed by the tributaries in Guizhou Province (Mengjiang River,Bawang River,Caodu River,and Liudong River),which are the focus of flood forecasting.The total average relative peak flow error and the average relative flood volume error in the river system flood forecasting scheme are both 10%,and the average deterministic coefficients are above 0.75.The overall results are relatively accurate.Therefore,the river system flood forecasting scheme for the Longtan Hydropower Station interval can be applied to real-time flood operation forecasting,and it lays a solid foundation for further improving the “forecast,early warning,rehearsal,and contingency plan” capability.